URGENSI PENGINTEGRASIAN REGULASI DOMESTIK RUANG UDARA UNTUK KEDAULATAN NEGARA DI ATAS WILAYAH INDONESIA - Daniel Payaw (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2026)
State sovereignty over airspace constitutes a fundamental principle of international law, affirming the exclusive right of a state to regulate and control its airspace without external interference. Although Indonesia has normatively adopted this principle through various national regulations and international legal instruments, the domestic regulation of airspace remains fragmented and characterized by overlapping institutional authorities. This study aims to analyze the legality of Indonesia’s airspace sovereignty and the urgency of integrating domestic regulations to establish a more structured and effective national air law system. The research employs a qualitative legal method with a normative juridical and descriptive-analytical approach, relying on library research of primary, secondary, and tertiary legal materials, including international legal instruments and national legislation concerning aviation, airspace security, and outer space affairs. The findings indicate that Indonesia’s sovereignty over its airspace possesses a strong legal foundation under both international and national law. However, regulatory disharmony and lack of systemic integration have weakened its practical effectiveness. Therefore, regulatory integration is a juridical and strategic necessity to transform declarative sovereignty into effective, operational, and adaptive sovereignty in response to modern aviation developments.